If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (0) = 4x + 6 0 = 4x + 6 Reorder the terms: 0 = 6 + 4x Solving 0 = 6 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 0 + -4x = 6 + 4x + -4x Remove the zero: -4x = 6 + 4x + -4x Combine like terms: 4x + -4x = 0 -4x = 6 + 0 -4x = 6 Divide each side by '-4'. x = -1.5 Simplifying x = -1.5
| 49x^2-25y^2+0=0 | | y=-2x+11 | | 49x^2-25y^2=0 | | y=4(-4)+6 | | 100-2*x=10+x | | (x+5)(x-5)=9 | | 5y-2x=0 | | 6/4064=x | | 9p-p=4p-11 | | 6/4064= | | 110-2*x=12+x | | -3x-8=2x+2 | | 9(4x+7)-4=8(7x+3)-3x | | 128x=48+4x | | x-3(0)=-6 | | 5m-5=n+10 | | 11-8x=65-22x | | 4(4x-3)=2(9x+5)-8 | | -3/4+1/2=r | | 18-6(x-2)=45 | | 9+2x=27 | | -3-5x=2x-11 | | -3-5=2x-11 | | 28-4n= | | 5x^2+10x-6=0 | | 6x-6*6=5 | | 8x^2+7x-7=0 | | .00000000023= | | 8x=128x | | 75-3x=33x+15 | | 6x-7y=11 | | 4x^2-25x+29=-5x+8 |